2017
DOI: 10.1371/journal.pone.0178562
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of dementia-related cognitive decline in a large mental health records derived patient cohort

Abstract: BackgroundModeling trajectories of decline can help describe the variability in progression of cognitive impairment in dementia. Better characterisation of these trajectories has significant implications for understanding disease progression, trial design and care planning.MethodsPatients with at least three Mini-mental State Examination (MMSE) scores recorded in the South London and Maudsley NHS Foundation Trust Electronic Health Records, UK were selected (N = 3441) to form a retrospective cohort. Trajectorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
25
0
3
Order By: Relevance
“…In accordance with previous studies, we observed great heterogeneity in the longitudinal course of dementia . In both our samples, a clear correlation was observed between MMSE and IADL trajectories (NACC: r = .61, P < .001; 4C: r = .79, P < .001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous studies, we observed great heterogeneity in the longitudinal course of dementia . In both our samples, a clear correlation was observed between MMSE and IADL trajectories (NACC: r = .61, P < .001; 4C: r = .79, P < .001).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies, we observed great heterogeneity in the longitudinal course of dementia. 10,12,31 In both our samples, a clear correlation was observed between MMSE and IADL trajectories (NACC: r = .61, P < .001; 4C: r = .79, P < .001). This indicates that those declining more quickly than other participants on one outcome measure tend to decline more quickly on the other outcome as well.…”
Section: Comparison With Other Studies and Potential Mechanismsmentioning
confidence: 55%
“…In people with dementia, these symptoms may contribute to a feeling of distress and discomfort, and are associated with a poorer quality of life [ 2 5 ]. Furthermore, more severe NPS have been found to be associated with an accelerated cognitive decline [ 6 , 7 ] and increased mortality [ 8 ], but the results regarding increased mortality are inconsistent [ 9 ]. NPS tend to increase depression [ 10 ] and reduce quality of life [ 11 ] for next of kin.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large cohort (N=3441) derived from UK electronic health records, Baker et al (2017) identified 6 different trajectories of MMSE progression as well. 32 Unfortunately, this study did not stratify patients based on their moment of dementia onset or diagnosis. Consequently, the observed heterogeneity may be largely attributable to differences in disease stage at baseline, hampering inferences about the progression of AD and its predictors.…”
Section: Discussionmentioning
confidence: 99%